Investigation of molecular interactions of antibiotic Doxycycline Hyclate with palmitic acid - P.E. Akilandeswari, M.G. Mohammed Kamil, C. Roumana, G. Velraj (Recent Research in Science and Technology, 2009)
Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The Dilute solution viscometric technique is employed to find the molecular interactions between the non-Newtonian Doxycycline hyclate and the essential saturated fatty acid, Palmitic acid in the common solvent Ethyl methyl ketone. The viscometric parameters Ã‚Âµ, ÃŽÂ± and ÃŽÂ² identifies the molecular interactions at physiological temperatures. The conformity of interaction has been attempted by the ultrasonic velocity; and the related acoustical parameters at temperatures 303, 310 and 313K. The chemical nature of the blend solutions have been identified through refractometric technique. The behaviour of these parameters explains the molecular interactions on the basis of solute-solute and solute-solvent interactions.